Developing Small Molecule Therapeutics for the Initial and Adjunctive Treatment of Snakebite - Tommaso C. Bulfone; Stephen P. Samuel; Philip E. Bickler; Matthew R. Lewin (Journal of Tropical Medicine)
The World Health Organization (WHO) recently added snakebite envenoming to the priority list of Neglected Tropical Diseases (NTD). It is thought that ~75% of mortality following snakebite occurs outside the hospital setting, making the temporal gap between a bite and antivenom administration a major therapeutic challenge. Small molecule therapeutics (SMTs) have been proposed as potential prereferral treatments for snakebite to help address this gap. Herein, we discuss the characteristics, potential uses, and development of SMTs as potential treatments for snakebite envenomation. We focus on SMTs that are secretory phospholipase A2 (sPLA2) inhibitors with brief exploration of other potential drug targets on venom molecules.